Closing the translation gap for justice requirements in international research. Issue 9 (16th March 2012) - Pratt, Bridget; Zion, Deborah; Lwin, Khin Maung; Cheah, Phaik Yeong; Nosten, Francois; Loff, Bebe
Abstract : Bioethicists have long debated the content of sponsors and researchers' obligations of justice in international clinical research. However, there has been little empirical investigation as to whether and how obligations of responsiveness, ancillary care, post-trial benefits and research capacity strengthening are upheld in low- and middle-income country settings. In this paper, the authors argue that research ethics guidelines need to be more informed by international research practice. Practical guidance on how to fulfil these obligations is needed if research groups and other actors are to successfully translate them into practice because doing so is often a complicated, context-specific process. Case study research methods offer one avenue for collecting data to develop this guidance. The authors describe how such methods have been used in relation to the Shoklo Malaria Research Unit's vivax malaria treatment (VHX) trial (NCT01074905 ). Relying on the VHX trial example, the paper shows how information can be gathered from not only international clinical researchers but also trial participants, community advisory board members and research funder representatives in order to: (1) measure evidence of responsiveness, provision of ancillary care, access to post-trial benefits and research capacity strengthening in international clinical research; and (2) identify the contextual factors and roles and responsibilities that were instrumental in the fulfilment of these ethical obligations. Such empirical work is necessary to inform the articulation of obligations of justice in international research and to develop guidance on how to fulfil them in order to facilitate better adherence to guidelines' requirements.